'Indo-Mauritians' and the Indian Ocean: literacy accounts and anthropological readings. Issue 2 (4th May 2017) - Claveyrolas, Mathieu
ABSTRACT: Starting from a broad historical overview, and focusing on the main group in the Mauritian population (the Hindu descendants of indentured laborers), this paper goes through the many and changing narratives of indenture, as a 'domesticating paradigm' promoted in both literature and identity discourses. It deals with three connected questions, each helping us understand the relations between Mauritius and the Indian Ocean. First, is the issue of the links between so-called Indo-Mauritians and India, the territories their ancestors came from: have they been severed or enhanced? Second, comes the auto-representations and status of Mauritius: is it an ideal center-of-the-world, or a relegated island lost in the Indian Ocean? Third are the representations Indo-Mauritians have of their original migrations, through the crossing of the Indian Ocean. A final point notes the poor inclusion of Mauritius in the Indian Ocean compared with the powerful and exclusive link between India and Mauritius.